Actively Controlled Frequency-Agile Fano-Resonant Metasurface for Broadband and Unity Modulation - Yang, Ruisheng; Fu, Quanhong; Fan, Yuancheng; Xu, Jing; Zhu, Wei; Cai, Weiqi; Zhang, Fuli (Frontiers in Physics, 2021)
The active control to the local resonant mode of metasurface is a promising route for improving the operation bandwidth limitation of metasurface. Here, we propose and experimentally demonstrated the active tunabilities in a frequency-agile Fano-resonant metasurface. The metasurface with a pair of asymmetric split ring resonators (ASRRs) is integrated with double varactor diodes for active control of the sharp Fano resonance. It is found that the sharp Fano-type spectrum appears due to the near-field interferences between the collective electric and magnetic dipole modes. The physical insight is revealed through local field analysis, multipole decomposition and temporal coupled-mode theory (TCMT). It is also found that the metasurface can be employed as a broadband and unity modulator. Hopefully, our results could inspire sophisticated electrically controlled photonic devices with novel functions.